Synthesis and Characterization of Magnetite/Carbon Nanocomposite Thin Films for Electrochemical Applications - Pang, Suh Cem; Khoh, Wai Hwa; Chin, Suk Fun (Elsevier Ltd., 2011)
Stable colloidal suspension of magnetite/starch nanocomposite was prepared by a facile and aqueous-based chemical precipitation method. Magnetite/carbon nanocomposite thin films were subsequently formed upon carbonization of the starch component by heat treatment under controlled conditions. The initial content of native sago starch as the carbon source was found to affect the microstructure and electrochemical properties of the resulted magnetite/carbon nanocomposite thin films. A specific capacitance of 124 F/g was achieved for the magnetite/carbon nanocomposite thin films as compared to that of 82 F/g for pure magnetite thin films in Na2SO4 aqueous electrolyte